Metabolite profiles of the fertile and non-fertile soils for the planting of Mangifera indica L. - Jan Jam, Mohammad Zulfadhly; Mohd Samsudin, Nur Syaza; Amir Fuzil, Amir Anwar Raziq; Mohd Aziz, Khawarizmi; Abdullah, Muhamad Azwat; Rofiee, Mohd Salleh; Teh, Lay Kek; Salleh, Mohd Zaki (GADING Journal of Science and Technology, 2023)
Mangifera indica L.is locally known as Harumanis. It is one of the popular cultivars of mango trees in Malaysia planted in the north of Peninsular Malaysia especially in Perlis because of the unique climate and soil condition. This study was carried out to differentiate the metabolites profiles of the fertile and non-fertile soil in Mangifera indica L. plantation. Soil from which the Harumanis was planted was sampled and the metabolites were profiled using LC/MS-QTOF. Soils were sampled from 2 different areas of the same farm, the fertile and non-fertile soil areas. The samples were dried, and the soil metabolites were extracted for metabolomics analysis using LC/MS-QTOF. A total of 307 metabolites were detected but only 13 metabolites were significantly differentiated between the fertile and non-fertile soil (p<0.05, log2FC>1.0). The metabolites were characterised to different groups of compounds such as pesticide, alkaloid, amino acid, terpenoid and carbamate. Fertile soil may contain beneficial metabolites that influence the soil quality which affect the optimum growth of Harumanis.